Personality in Captive Ring-tailed Lemurs (Lemur Catta): Trait Structure and the Interaction with Dominance Hierarchy and Zoo Visitor Effects - Fleming, Camille (My University, 2008)
Personality ratings for a captive group of ring-tailed lemurs were obtained and factor analysis revealed four personality factors labelled Dominance, High Neuroticism/Low Conscientiousness, Extraversion and Agreeableness. The study also explored whether grooming behaviour could be used as a dominance index and results indicated that higher-ranking lemurs were less likely to initiate grooming to other lemurs. Correlations between grooming behaviour and the personality factors indicated that Extraversion was correlated with average grooming received and High Neuroticism/Low Neuroticism was correlated with average grooming initiated. Finally, zoo visitor effects were examined and significant effects were found for audience size on locomotion and affiliative behaviour and there was an interaction between audience size and audience activity for agonisic behaviours. Correlations between these behaviours and the personality factors revealed a significant relationship between Agreeableness and agonistic behaviour. As the study is the first known exploration in to lemur personality, future research on other samples of lemurs is needed to discover if the personality factor structure is stable across different environments.
Keywords: primate; personality; zoo; grooming